Selective modulation of the bone remodeling regulatory system through orthodontic tooth movement—a review - Danz, Jan Christian; Degen, Martin (Frontiers in Oral Health, 2025)
Little is known about how tissues mediate the ability to selectively form or resorb bone, as required during orthodontic tooth movement (OTM), facial growth, continued tooth eruption and for healing after fractures, maxillofacial surgical repositioning or implant dentistry. OTM has the unique ability to selectively cause apposition, resorption or a combination of both at the alveolar periosteal surface and therefore, provides an optimal process to study the regulation of bone physiology at a tissue level. Our aim was to elucidate the mechanisms and signaling pathways of the bone remodeling regulatory system (BRRS) as well as to investigate its clinical applications in osteoporosis treatment, orthopedic surgery, fracture management and orthodontic treatment. OTM is restricted to a specific range in which the BRRS permits remodeling; however, surpassing this limit may lead to bone dehiscence. Low-intensity pulsed ultrasound, vibration or photobiomodulation with low-level laser therapy have the potential to modify BRRS with the aim of reducing bone dehiscence and apical root resorption or accelerating OTM. Unloading of bone and periodontal compression promotes resorption via receptor activator of nuclear factor κB-ligand, monocyte chemotactic protein-1, parathyroid hormone-related protein (PTHrP), and suppression of anti-resorptive mediators. Furthermore, proinflammatory cytokines, such as interleukin-1 (IL-1), IL-6, IL-8, tumor necrosis factor-α, and prostaglandins exert a synergistic effect on bone resorption. While proinflammatory cytokines are associated with periodontal sequelae such as bone dehiscence and gingival recessions, they are not essential for OTM. Integrins mediate mechanotransduction by converting extracellular biomechanical signals into cellular responses leading to bone apposition. Active Wnt signaling allows β-catenin to translocate into the nucleus and to stimulate bone formation, consequently converging with integrin-mediated mechanotransductive signals. During OTM, periodontal fibroblasts secrete PTHrP, which inhibits sclerostin secretion in neighboring osteocytes via the PTH/PTHrP type 1 receptor interaction. The ensuing sclerostin-depleted region may enhance stem cell differentiation into osteoblasts and subperiosteal osteoid formation. OTM-mediated BRRS modulation suggests that administering sclerostin-inhibiting antibodies in combination with PTHrP may have a synergistic bone-inductive effect. This approach holds promise for enhancing osseous wound healing, treating osteoporosis, bone grafting and addressing orthodontic treatments that are linked to periodontal complications.